Nitrogen fertilizers manufactured using wind power: greenhouse gas and energy balance of community-scale ammonia production. (16th November 2015) - Tallaksen, Joel; Bauer, Fredric; Hulteberg, Christian; Reese, Michael; Ahlgren, Serina
Abstract: The paper presents a cradle-to-gate life cycle assessment of production of ammonia using wind power. The ammonia is intended to substitute for nitrogen fertilizer produced from fossil resources. The studied system is designed to supply a rural community with fertilizer based on renewable energy and is, therefore, smaller than industrial fossil ammonia production systems. Two contrasting cases examine the impact of the location of the system, investigating the dependence on the regional energy system (background system) to balance demand and supply of energy in the ammonia production system (foreground system). The results show that wind-based ammonia production can significantly decrease fossil energy inputs and greenhouse gas emissions compared to conventional production, but that the use of energy from the background system severely impacts the environmental performance, especially in regions where fossil fuels dominate the energy system. Highlights: Ammonia is the standard source of nitrogen for agricultural fertilizers. Energy use and GHG were modeled at a wind powered ammonia production facility. Wind based ammonia production is still dependent on background energy system. Fossil energy use for renewable ammonia was 149% to −108% of conventional ammonia. Results show high sensitivity to background grid electrical system fossil energy use.